Securing RF Communication Using AES-256 Symmetric Encryption: a Performance Evaluation - Jamaluddin, A.; N. Mohamed, N.; Hashim, H. (International Journal of Engineering and Technology, 2018)
Radio Frequency (RF) communication plays a vital role for sensor node data transmission, which typically runs on top of lightweight protocol such as Constrained Application (CoAP) and Trivial File Transfer Protocol (TFTP). Introducing a cryptographic scheme to the process is known to be the common and most efficient method to protect RF communication. This paper presents the performance comparison of AES-encrypted data transmission over RF communication via Raspberry Pi boards, experimented on a client-server architecture. The performance analysis is measured based on throughput metric and the transmission time delay when sending three types of payload which are, a plaintext data, a ciphertext with padding and a ciphertext without padding. The result from the study indicates that there is a significant difference in data transmission time between the three types of data due to the data expansion factor. The result also showed that adding padding to the ciphertext has increased the data size slightly but not significant enough to affect transmission time of ciphertext.Â